Aktivitas Antibakteri Ekstrak Etanol Daun Jengkol (Archidendron pauciflorum Benth.) Terhadap Bakteri Staphylococcus epidermidis dan Pseudomonas aeruginosa - Arisetya, Dian; Sapitri, Alfi; Asfianti, Vivi; Lubis, Retnita Ernayani (Program Studi S1 Farmasi, STIKES Senior, Medan, 2025)
Archidendron pociflorum benth is a nutritious plant that is used as a traditional medicine that is often used by society. Secondary metabolic compounds contained in archidendron pociflorum leaves are alkaloids, flavonoids, tannins and saponin. The purpose of this research is to know the antibacterial activity of the extract of archidendron pociflorum leaf ethanol from the Staphylococcus epidermidis and Pseudomonas areuginosa bacteria. Research conducted experimentally including the collection and processing of archidendron pociflorum leaves. The powder simplisia leaves archidendron pociflorum then be done characteristic and macerated using ethanol 96%. Further extracts of archidendron pociflorum leaf ethanol in the phytochemical screening and carried out test antibacterial activity against Staphylococcus epidermidis and pseudomonas areuginosa bacteria use the diffusion method to make it with disc paper. Results characteristic simplisia of archidendron pociflorum leaves obtained water content of 8.1%, water soluble sari content of 9.49%, soluble pollen content of 7.61%, total ash content 3.80%, ash content of insoluble acid 14.67%. Scining extracts of archidendron pociflorum leaves and simplisia indicate the presence of alkaloid, tannins, saponin, flavonoids. The test results of antibacterial activity indicate that the leaf ethanol extract of the staphylococcus epidermidis bacteria with a concentration of 80%, 60%, 40%, 20% respectively had an obstacle zone of 13.6 mm, 12.3 mm, 11, 4mm and 9.7 mm. While in bacteria pseudomonas areuginosa with a concentration of 80%, 60%, 40%, 20% respectively has a inhibitory zone of 14.3 mm, 13.1 mm, 11.2 mm and 10.3 mm. Archidendron pociflorum leaf ethanol extract has been effective against antibacterial activity with a concentration of 80% against bacteria staphylococcus epidermidis and pseudomonas aureginosa.